Evaluation of a Quantitative Taqman Real-Time PCR Assay to Measure Proviral load from Human Immunodeficiency Virus Type 1 individuals - Suguna Elumalai; Chitralekha Saikumar; Florida Tilton; Lakshmi Krishnasamy (Journal of Pure and Applied Microbiology, 2022)
Human Immunodeficiency Virus (HIV) is a virus belonging to the family Retroviridae. HIV – 1 is found to be predominant in India and many parts of Africa. The intention of this study was to quantify the HIV Proviral Deoxyribonucleic Acid (DNA) from newly infected HIV-1 individuals. Fifty patients who were tested positive for HIV were included in this study. Proviral Ribo Nucleic Acid (RNA) was extracted by QIAmp® RNA Mini Kit (QIAGEN, Germany) method. Complementary Deoxyribo Nucleic Acid (cDNA) was synthesized by using Invitrogen Superscript III cDNA synthesis Kit (USA). This cDNA was subjected to Polymerase Chain Reaction (PCR) and Gene cloning by transformation method. The quantification of Real time PCR was done by Applied Bio-System (ABI)-Prism 7700. A linear standard curve was obtained 10 copies to 106 copies per reaction. The assay had good analytic sensitivity and linear dynamic range greater than 6 logs. From the results obtained in this study, It was concluded that Taqman Real-Time PCR Assay plays a major role in monitoring the HIV infected patients in routine diagnostics and clinical practice.